2021
DOI: 10.1002/pd.6034
|View full text |Cite
|
Sign up to set email alerts
|

Low fetal fraction in cell‐free DNA testing is associated with adverse pregnancy outcome: Analysis of a subcohort of the TRIDENT‐2 study

Abstract: Objectives To assess the association between low fetal fraction (FF) in prenatal cell‐free DNA (cfDNA) testing and adverse pregnancy outcomes. Methods We conducted a retrospective cohort study of participants of the TRIDENT‐2 study (Dutch nationwide government‐supported study offering cfDNA screening for fetal aneuploidies) who received a failed test result due to low FF (<4%) between April 2017 until February 2018. Outcome measures included pregnancy‐induced hypertension (PIH), pre‐eclampsia (PE), small for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
4
25
1
Order By: Relevance
“…Our results support that the possible use of FFs on clinical cfDNA screening reports for the prediction of adverse pregnancy outcomes deserves further investigation in larger prospective studies. [21][22][23][24] Fetal cells enter maternal circulation through trophoblast apoptosis, and thus it is not surprising that pathologies affecting the placenta would impact the FF. 36 The pathophysiology of HPD, specifically preeclampsia, is thought to be due to abnormal trophoblast invasion of uterine vessels during placentation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results support that the possible use of FFs on clinical cfDNA screening reports for the prediction of adverse pregnancy outcomes deserves further investigation in larger prospective studies. [21][22][23][24] Fetal cells enter maternal circulation through trophoblast apoptosis, and thus it is not surprising that pathologies affecting the placenta would impact the FF. 36 The pathophysiology of HPD, specifically preeclampsia, is thought to be due to abnormal trophoblast invasion of uterine vessels during placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that there is an increase in both fetal and total cfDNA in women with preeclampsia and other hypertensive disorders of pregnancy (HPD), but the FF remains low due to the greater percentage of maternal cfDNA in the plasma. [21][22][23][24] Moreover, it has recently been shown that there is a positive correlation between FF and placental proteins such as beta-hCG, PAPP-A, and PlGF, all of which are biomarkers of placental function. 25 In a case-control study that included euploid, trisomy 21, and trisomy 18 pregnancies, Ashoor et al found that FF correlated with levels of maternal PAPP-A and beta-hCG, which are known placenta-derived serum biomarkers used to screen for aneuploidy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations